Analisis Daya Saing Sektor Pertanian Dalam Upaya Peningkatan Pembangunan Pertanian Di Kabupaten Lampung Timur - Novita; Novia Ambar Sari (lembaga penelitian universitas swadaya gunung jati, 2024)
This research aims to analyze the competitiveness of the agricultural sector in East Lampung Regency and policies to increase the competitiveness of the agricultural sector. The data used as a basis for the analysis are primary data and secondary data. The competitiveness of the agricultural sector was analyzed descriptively and using Location Quotient (LQ) analysis. Furthermore, to formulate policies in order to increase the competitiveness of the agricultural sector, SWOT analysis is used. One way of developing a region is to reduce differences in the level of development or development between regions, then each region is free to determine which sectors are prioritized for development. The agriculture, forestry and fisheries sectors of East Lampung Regency are the base sectors, so that agricultural sector production not only meets its own needs but can be exported to other regions. This means that the agricultural sector of East Lampung Regency has quite high competitiveness. East Lampung Regency is one of the districts that has more sources of livelihood in the agricultural sector than other fields and is the second largest rice contributing district in Lampung Province. Several things related to land area, amount of production and level of productivity of a commodity are indicators of competitiveness in this research. For the development of a region, the thing that can be prioritized is the sector that is the basis of the people's lives. The agricultural sector of East Lampung Regency is a leading sector in the fields of food crops, horticulture, plantations, forestry, fisheries and animal husbandry. So in efforts to implement agricultural development, the government needs to focus on developing superior commodities. Commodities that can be favored are rice, corn and cassava through increasing productivity, improving quality and post-harvest processing.Keywords: Competitiveness, Agricultural Sector, Agricultural Development, LQ and SWOT Analysis